Detached low energy house - Radulescu, Raul-Ionut (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Bakalářská práce je zaměřena na řešení výstavby "Samostatného nízkoenergetického domu" ve formě projektové dokumentace.Dům je určen pro jednu rodinu. Nachází se na parcele číslo 664/42, k.ú. Medlov okres(Brno-venkov).Dům je nepodsklepený a má dvě podlaží s žádnou garáží. Objekt je z prefabrikovaného betonu, jedná se o budovu s plochou střechou se sklonem 1 °.

The bachelor’s thesis is aimed on the solution of construction of "Detached low energy house" in form of project documentation. The house is intended for one family. It is located on parcel number 664/42, cadastral area Medlov (Brno-venkov) district. The house is without basement and has two stories with no garage.. The object is pre-cast concrete building with flat roof with a slope of 1 °.
Detached low energy house
Keywords: rodinný dům; samostatně stojící; příhradový nosník; betonové panely; ytong bloky; větraná střecha; nízkoenergetický standard; Family house; detached; timber truss system; concrete panels; ytong blocks; cold roof; low energy.